Prenatal vaccination education intervention improves both the mothers' knowledge and children's vaccination coverage: Evidence from randomized controlled trial from eastern China. Issue 6 (3rd June 2017) - Hu, Yu; Chen, Yaping; Wang, Ying; Song, Quanwei; Li, Qian
ABSTRACT: Objectives: To verify the effectiveness of prenatal vaccination education intervention on improving mother's vaccination knowledge and child's vaccination status in Zhejiang province, eastern China. Methods: Pregnant women with ≥ 12 gestational weeks were recruited and randomly assigned into the intervention group and the control group. The intervention group were given a vaccination education session while the control group were not. Two round surveys were performed before and 3 months after the intervention. The vaccination status of child was extracted at 12 months of age from immunization information system. The differences of the vaccination knowledge, the coverage, the completeness and the timeliness of vaccination between 2 groups were evaluated. The effectiveness of vaccination education intervention was assessed, under the control of the other demographic variables. Results: Among the 1252 participants, 851 subjects replied to the post-survey. Significant improvements of vaccination knowledge between the pre- and the post- survey in the intervention group were observed (Mean ± S.D:1.8 ± 1.1 vs. 3.7 ± 1.2 for vaccines score and 2.7 ± 1.5 vs. 4.8 ± 1.0 for vaccine policy score, respectively). The coverage of fully vaccination was significantly higher in the intervention group (90.0% vs. 82.9%, P <0.01). The timeliness of fully vaccination was significantly higher in the intervention group (51.9% vs. 33.0%, P <0.01). In the intervention group, pregnant women were more likely to be with high score of knowledge (OR = 5.2, 95% CI : 2.6–8.8), and children were more likely to complete the full series of vaccination (OR = 3.4, 95% CI : 2.1–4.8), and children were more likely to complete the full series of vaccination in a timely manner (OR = 2.3, 95% CI : 1.6–3.5). Conclusions: Vaccination education in the pregnant women can effectively improve the knowledge regarding immunization and increase the coverage, the completeness and the timeliness of childhood vaccination. Strong partnership needs to be established between the obstetricians and the vaccination staff to improve the performance of NIP.